Featured Cover. (5th April 2021) - Lu, Qinghua; Binh Tran, An; Weber, Ingo; O'Connor, Hugo; Rimba, Paul; Xu, Xiwei; Staples, Mark; Zhu, Liming; Jeffery, Ross
Abstract : The cover image is based on the Research Article Integrated model-driven engineering of blockchain applications for business processes and asset management by Qinghua Lu et al., https://doi.org/10.1002/spe.2931